2012
DOI: 10.1155/2012/498062
|View full text |Cite
|
Sign up to set email alerts
|

Do Breast Cancer Patients Tested in the Oncology Care Setting ShareBRCAMutation Results with Family Members and Health Care Providers?

Abstract: BRCA genetic test results provide important information to manage cancer risk for patients and their families. Little is known on the communication of genetic test results by mutation status with family members and physicians in the oncology care setting. As part of a longitudinal study evaluating the impact of genetic counseling and testing among recently diagnosed breast cancer patients, we collected patients' self-reported patterns of disclosure. Descriptive statistics characterized the sample and determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…11,27 Physicians also fell short in their counseling about the implications of test results, focusing heavily on surgical options and neglecting to explore familial implications, emotional impacts, or social support, though each of these is an essential component of the genetic counseling process. [42][43][44][45] Furthermore, though considerable attention was devoted to ELSI issues in the web-based and control curriculum materials, only half of the participants talked with the SP about medical record confidentiality, insurance discrimination, and federal legal protections. Even fewer examined employment discrimination concerns, and none explored the important issue of social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Physicians also fell short in their counseling about the implications of test results, focusing heavily on surgical options and neglecting to explore familial implications, emotional impacts, or social support, though each of these is an essential component of the genetic counseling process. [42][43][44][45] Furthermore, though considerable attention was devoted to ELSI issues in the web-based and control curriculum materials, only half of the participants talked with the SP about medical record confidentiality, insurance discrimination, and federal legal protections. Even fewer examined employment discrimination concerns, and none explored the important issue of social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine barriers that prevent Bahamian women from communicating positive BRCA mutation results to their at‐risk relatives. Compared to studies in non‐Bahamian populations in the United States and Canada, the number of relatives in the Bahamas who came for genetic counseling was low . In our study, when the proband was the person disclosing their result to relatives, 8% of relatives came for genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, when the proband was the person disclosing their result to relatives, 8% of relatives came for genetic counseling. In contrast, other studies have found that between 80% and 100% of relatives were informed of the proband's result when the proband was tasked with informing them . The uptake of genetic counseling by relatives was similar in our population to that of other studies when at‐risk relatives were informed directly by the genetic counselor (84%).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for the study are reported in greater detail in previous reports [26,27] and are briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…The paper reported differences in outcomes related to knowledge, cancer-related distress, and decisional conflict between patients who attended pretest genetic counseling prior to, versus those who attended after definitive surgical treatment [26]. A second paper reported on communication of test results to family members and providers among a subset of BC survivors who pursued genetic testing [27]. …”
Section: Introductionmentioning
confidence: 99%